Factors influencing the Adherence to Covid-19 Prevention Guidelines among the Elderly in Mbarara Regional Referral Hospital, Mbarara District. A Cross-sectional Study. - Boaz Mugisha Nuwabiine (Student's Journal of Health Research, 2022)
Background:  This study assessed the factors influencing the adherence to Covid-19 prevention guidelines among the elderly while specifically looking at the level of adherence, the individual the social factors influencing adherence to Covid-19 prevention guidelines among the elderly in Mbarara Regional Referral Hospital, Mbarara district. Methodology: The study adopted a cross-sectional and descriptive research design with a quantitative approach where a pretested questionnaire designed based on the specific objectives was used to collect data from 194 participants following informed consent. Findings:  The majority of the respondents (61.9%) were female, those aged 60-80 years were 150 (77.3%), Catholics were 68 (35.1%), 134 (69.1%) were married and 134 (69.1%) had not attained any formal education. Also, the majority of the respondent 160 (82%) knew what adherence to Covid-19 prevention guidelines meant, 90 (56%) ever adhered to Covid-19 prevention guidelines, 149 (77%) did not adhere to all Covid-19 prevention guidelines and 115 (59.3%) were always with their friends and relatives. Additionally, most of the respondents (46.2%) perceived Covid-19 as a disease for the white people, (68.0%) with chronic diseases were adherent, history of being infected with Covid-19 influenced adherence (52%), and having enough knowledge was associated with good adherence (60.3%).  Conclusion:  The study, therefore, concluded that the level of adherence to Covid-19 prevention guidelines among the elderly was low majorly due to high-risk perception of contracting Covid-19, dissatisfaction with Covid-19 prevention guidelines, use of medicinal plants for treating Covid-19 related symptoms, area of residence and living in a homestead with many occupants.  Recommendation:  The study recommends that the country's Ministry of Health, through its decentralized systems, should use health workers to sensitize the public on COVID-19 through various fora, including community outreach since the population is more likely to trust information from health workers and any other trusted source leading to high adherence.